Mobile-Assisted Language Learning Based Using Scientific Approach to Improve Students Vocabulary - perwita, Tri; Asmana, Candra Hadi; Arifani, Yudhi (Universitas Muhammadiyah Gresik, 2020)
One of the hard sections of learning the target language for English language learners is vocabulary. Vocabulary plays a significant part in language learning because without vocabulary the students cannot master 4 skills (speaking, listening, reading, and writing). So many problems were found in learning vocabulary which influence students’ vocabularies mastery and to solve it the researcher addresses the alternative strategy which can be used for teaching learning vocabulary. Based on previous studiess technology gave the positive effect on learning English. Thus, making different with the previous studies, the researcher applied MALL based using scientific Approach to teaching vocabulary. The objective of the study is to find out the significant effect of MALL based using scientific Approach to improve students’ vocabulary. The design of this study was quasi experiment design. The researcher chose eight grade students of SMPN 4 Babat which totally consisted of 48 students. The researcher chose the sample of the study through population sampling. The sample was divided 24 students of VIII-A as experiment group and 24 students of VIII-B as control group. The data was collected by using pre-test and post-test about active and passive vocabulary. After getting the data, the researcher analyzed the data using SPSS 16.00 and independent Sample T-test. The research finding showed that there was significant difference between experimental group and control group. It has been proven by the result of sig. (2-Tiled) is .002. the sig (2-Tiled) is lower 0.05 (0.001 < 0.05). So, null hypothesis (Ho) can be rejected. It means that MALL based using scientific approach significantly affects students vocabulary. The researcher concluded that MALL based using scientific approach give positive effect on students’ vocabulary ability. The researcher suggests the English teacher to implement MALL based using scientific approach as an alternative strategy in teaching learning process. For the next researcher, they can implement MALL for higher level students’ using other media.